การศึกษาพลังอำนาจภายในของแม่เลี้ยงเดี่ยวในสังคมไทย - สงวนวงษ์ ณัฐกา; รัตนโรจน์สกุล พิศมัย; ศรีสวัสดิ์ พัชราภรณ์; มณีศรีขำ ทศวร (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2018)
บทคัดย่อ ครอบครัวแม่เลี้ยงเดี่ยวที่มีจำนวนเพิ่มขึ้นอย่างรวดเร็วเป็นปรากฏการณ์ที่หลายภาคส่วนในสังคมให้ความสำคัญ ทั้งนี้พลังอำนาจภายในของแม่เลี้ยงเดี่ยวเป็นปัจจัยสำคัญที่ส่งผลต่อความสามารถในการรับมือกับความเปลี่ยนแปลงและประคับประคองครอบครัวให้ทำหน้าที่ได้อย่างมั่นคง แต่ยังไม่มีการให้นิยามพลังอำนาจภายในของแม่เลี้ยงเดี่ยวในเชิงแนวคิดทฤษฎีในบริบทสังคมไทย การวิจัยครั้งนี้จึงมีวัตถุประสงค์เพื่อศึกษาความหมายและคุณลักษณะพลังอำนาจภายในของแม่เลี้ยงเดี่ยวในบริบทสังคมไทย โดยใช้การวิจัยเชิงคุณภาพตามแนวทางการสร้างทฤษฎีจากฐานราก กลุ่มเป้าหมายคือแม่เลี้ยงเดี่ยวอายุระหว่าง 30-45 ปี ในกรุงเทพมหานคร ที่มีประสบการณ์เป็นแม่เลี้ยงเดี่ยวมาไม่น้อยกว่า 3 ปี เจาะจงกลุ่มแม่เลี้ยงเดี่ยวที่มีฐานะทางเศรษฐกิจสังคมในระดับปานกลางลงมา และพิจารณาคัดเลือกเฉพาะแม่เลี้ยงเดี่ยวที่มีแนวโน้มพลังอำนาจภายในสูง คือสามารถปรับตัวผ่านวิกฤตการเปลี่ยนแปลงของครอบครัวมาสู่จุดที่มั่นคงได้ ซึ่งได้รับการแนะนำมาจากผู้ที่ทำงานใกล้ชิดกับแม่เลี้ยงเดี่ยวรวมทั้งการบอกต่อกันมา เก็บข้อมูลจากผู้ให้ข้อมูลหลักจำนวน 12 คน โดยการสัมภาษณ์เชิงลึก มีการวิเคราะห์ข้อมูลเชิงเนื้อหาจากการสัมภาษณ์เพื่อนำไปสร้างข้อเสนอเชิงทฤษฎี และยืนยันข้อเสนอเชิงทฤษฎีโดยผู้มีประสบการณ์ทำงานกับแม่เลี้ยงเดี่ยว ผลการวิจัย แสดงให้เห็นความหมายและคุณลักษณะพลังอำนาจภายในของแม่เลี้ยงเดี่ยว 5 คุณลักษณะ คือ (1) การรับรู้และเชื่อในความสามารถของตนเอง คือ การรับรู้และเชื่อความสามารถตนเองในการจัดการปัญหา ซึ่งหล่อหลอมจากประสบการณ์ การเรียนรู้ ตัวแบบ การได้รับการยอมรับและความสำเร็จในการเป็นแม่เลี้ยงเดี่ยว (2) การยอมรับและตระหนักในตนเอง คือ การยอมรับตนเอง การคิดพึ่งตนเอง และการเห็นคุณค่าศักดิ์ศรีของตนเอง (3) การมีมุมมองด้านบวก คำสำคัญ : พลังอำนาจภายใน พลังอำนาจภายในของแม่เลี้ยงเดี่ยว แม่เลี้ยงเดี่ยวในสังคมไทย ดังกล่าวนำไปเป็นข้อมูลในการออกแบบกระบวนการให้คำปรึกษาแบบรายบุคคลเพื่อเสริมพลังอำนาจภายในของแม่เลี้ยงเดี่ยวต่อไป คำสำคัญ : พลังอำนาจภายใน พลังอำนาจภายในของแม่เลี้ยงเดี่ยว แม่เลี้ยงเดี่ยวในสังคมไทย ABSTRACT The rapidly increasing number of single-mother families is the phenomena that several sectors in society give priority. Although personal power of single-mother is an important factor affecting capability to deal with change, and support her family to do its duties, there was no theoretical definition of personal power of single-mothers in the context of Thai society. This research aimed to study meaning and characteristics of personal power of single-mother in Thai society context using qualitative research with as grounded theory method. Target group is single-mothers aged between 30 and 45 years old who lives in Bangkok, with experience of being single mothers longer than 3 years and socioeconomic status in moderate and level lower. Single mothers having a tendency to have high personal power that could adapt themselves through crisis of changes in families to the secure state were selected from a group of them recommended by persons who had worked closely with single mothers and Snowball Sampling. Information was collected from twelve key informants by in-depth interview. An analysis of the content from the interviews led to the theoretical proposal. The theoretical proposition was confirmed by experienced practitioners working with single mothers. The results of the research have shown meaning and five characteristics of single-mother’s personal power: (1) Recognition and belief in self-efficacy that is recognition and belief in self-efficacy to deal with problems which derived from experiences, learning, models, being acknowledged, and success of being single-mother (2) Self-acceptance and awareness are self-acceptance, thinking of self-reliance and awareness of self-honor (3) Positive thinking perspective is giving positive meaning or accepting different perspectives, creating meaning of life, and world and life understandings (4) Self-determination is decision to choose and act independently, setting possible goal of life for oneself, determination for action, and capability for solving problem (5) Seeing opportunity and social support is perception and using available support including capability to access knowledge to develop oneself. These results of the study would be information to design procedure of individual counseling to enhance personal power of single-mother in the future. Keywords : Personal Power, Personal Power of Single-Mother, Single-Mother in Thai Society